Tren Hadis di Masyarakat: Eksplorasi Perkembangan Tema Hadis Melalui Analisis Media Sosial Instagram - Tanggok, M Ikhsan; Yazid, Rizky; Khoiri, Ahmad; Ningrum, Dewi Aprilia (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Hadith Trends in Society: Exploration of the Development of Hadith Themes Through Instagram Social Media AnalysisThe discourse surrounding hadith wields a complex influence on society. Serving as the second guiding source after the Quran, hadith not only functions as a spiritual guide but also as a tool for legitimization and justification within various social and political contexts. In the contemporary digital era, especially on social media platforms such as Instagram, the understanding, interpretation, and utilization of hadith by the public have become highly significant. This virtual field research aims to investigate hadith trends within society through the analysis of three Instagram accounts: @nuonline_id, @tausiyahku_, and @muslimahnewsid, employing Norman Fairclough’s Critical Discourse Analysis (CDA) that explores the relationship between language, power, and ideology. In this study, Fairclough’s approach assists in delving into the use of hadith to construct and perpetuate power dynamics and social values through social media. Through this analysis, the research identifies three main social constructions of hadith: the preservation of NU identity and Aswaja values, viewing hadith as the moral foundation of the Nahdliyin; the reconstruction of social morality through reinterpretations of hadith relevant to contemporary social realities; and the indoctrination of ideology through exclusive and puritanical interpretations of hadith. These findings underscore the complexity of hadith in shaping the identity, morality, and ideology of contemporary society through social media. The implications of this study are profound, indicating that the understanding and application of hadith in social media not only reflect Islamic teachings but also specific socio-political influences and Islamic ideologies. Consequently, this research contributes vital insights into the trends of hadith within digital society, providing a foundation for further discussions about Islam and identity in this digital era.